Analysis of Strategic Cooperation Between PT. Pindad and MBDA (Matra Bae Dynamics Alenia) in Building Competitive Advantage for the Production of the Mistral Atlas Platform - Dodo Irmanto; Oviyan Patra; Hendy Suryana (Eduvest - Journal of Universal Studies, 2025)
This research aims to analyze the strategic cooperation between PT. Pindad, an Indonesian defense company, and MBDA (Matra Bae Dynamics Alenia), a leading missile systems company from France, in the development and production of the Mistral Atlas platform. This cooperation represents a crucial step in enhancing Indonesia's national defense capacity, particularly in addressing increasingly complex aerial threats. The research examines the collaboration process, technical challenges encountered, and the impact of this partnership on product innovation, competitive advantage, and company performance. The results of Structural Equation Modelling (SEM) analysis indicate that the strategic alliance between PT. Pindad and MBDA has a significant positive impact on enhancing product innovation, as manifested in product value. This alliance not only improves PT. Pindad's employees' skills through technology transfer but also contributes to greater product differentiation, which directly strengthens the company's competitive advantage. Product differentiation, in turn, has a significant impact on PT. Pindad's financial performance, thereby boosting the company's competitiveness in the global defense industry market. This research identifies key factors influencing the success of this strategic cooperation, including alliance quality, goal alignment, and employee skills. Based on these findings, the research provides recommendations for further development in the defense industry, particularly in enhancing product innovation and strengthening competitiveness through effective strategic collaboration. Thus, this research is expected to contribute significantly to understanding strategic cooperation in the defense industry and to support efforts to increase Indonesia's defense self-reliance.